2021
DOI: 10.3389/fpsyt.2021.670539
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Soft Signs (NSS) in Census-Based, Decade-Adjusted Healthy Adults, 20 to >70 Years of Age

Abstract: Neurological soft signs (NSS) represent minor neurological features and have been widely studied in psychiatric disease. The assessment is easily performed. Quantity and quality may provide useful information concerning the disease course. Mostly, NSS scores differ significantly between patients and controls. However, literature does not give reference values. In this pilot study, we recruited 120 healthy women and men to build a cross-sectional, census-based sample of healthy individuals, aged 20 to >7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…To date, numerous studies [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] have concluded that neurological soft signs (NSS) are found in variable proportions in patients with schizophrenia compared with healthy subjects or first-degree relatives and are associated with an early age of onset [ 6 , 11 ], a chronic course of illness [ 6 , 11 , 13 , 14 ], negative symptoms [ 15 , 16 , 17 ], lower IQ, lower education achievements, and a higher score on the Positive and Negative Syndrome Scale (PANSS). The presence of NSS translates into defects in sensory integration (SI), motor coordination (MC), integrative sensory functioning, and complex motor sequencing [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] have concluded that neurological soft signs (NSS) are found in variable proportions in patients with schizophrenia compared with healthy subjects or first-degree relatives and are associated with an early age of onset [ 6 , 11 ], a chronic course of illness [ 6 , 11 , 13 , 14 ], negative symptoms [ 15 , 16 , 17 ], lower IQ, lower education achievements, and a higher score on the Positive and Negative Syndrome Scale (PANSS). The presence of NSS translates into defects in sensory integration (SI), motor coordination (MC), integrative sensory functioning, and complex motor sequencing [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, NSSs that positively correlated with age in both healthy and OCD groups were motor coordination, sensory integration, and NES total scores. Bachmann et al (48) found that worsening motor function and sensory integration yielded the most important share of overall NSS increase between the ages of 50 and 60 years. Also, there is evidence that NSSs reduce toward late childhood and adolescence, and thus persistence of NSSs into later childhood can be a marker for atypical neurological function.…”
Section: Discussionmentioning
confidence: 99%